2000
DOI: 10.4049/jimmunol.165.9.5105
|View full text |Cite
|
Sign up to set email alerts
|

CD30 Signals Integrate Expression of Cytotoxic Effector Molecules, Lymphocyte Trafficking Signals, and Signals for Proliferation and Apoptosis

Abstract: Although CD30 has long been recognized as an important marker on many lymphomas of diverse origin and as activation molecule on B cells and T cells, its primary function has remained obscure. We now report that CD30 signals may serve to inhibit effector cell activity by integrating gene expression changes of several pathways important for cytotoxic NK and T cell effector function. In the large granular lymphoma line YT, CD30 signals down-regulate the expression of cytotoxic effector molecules, Fas ligand, perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 36 publications
3
62
0
1
Order By: Relevance
“…The classic stimulator, PMA-ion, induced an increase in CXCR4 mRNA (Figure 1), but the surface density of CXCR4 decreased ( Figure 3) primarily because of internalization. 33,44 Moreover, while this work was in progress, Muta et al 27 reported the surprising, unexpected finding that CD30 signals led to a 5.8-fold increase in CCR7 mRNA in YT lymphoma cells, arguing that, through CCR7, CD30 signals integrate lymphocyte trafficking, proliferation, and apoptosis. For personal use only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The classic stimulator, PMA-ion, induced an increase in CXCR4 mRNA (Figure 1), but the surface density of CXCR4 decreased ( Figure 3) primarily because of internalization. 33,44 Moreover, while this work was in progress, Muta et al 27 reported the surprising, unexpected finding that CD30 signals led to a 5.8-fold increase in CCR7 mRNA in YT lymphoma cells, arguing that, through CCR7, CD30 signals integrate lymphocyte trafficking, proliferation, and apoptosis. For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…For personal use only. on April 2, 2019. by guest www.bloodjournal.org From Thus, engagement of CD30 by CD153, which is associated preferentially with Th2-type effector responses, 19 regulates CXCR4 and CCR7 27 expression and delivers inhibitory signals, 20,27 leading to impaired clonal expansion of peripheral T cells, 21 sensitizing to TNFR1-dependent apoptosis, 3 and counteracting IgG and IgA production. 52 This cellularlevel regulation seems to have a counterpart in a number of conditions, sharing the tendency to selective compartmentalization of lowproliferating CD30 ϩ cells, which deliver locally anti-inflammatory cytokines, such as IL-4 and IL-10, whenever tested for 16 and which generate a molecular milieu characterized by features of immune suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD8ϩ T cells from subjects in group 1 had reduced gene expression of TNF family members, the cell surface expression of which is associated with susceptibility to activationinduced cell death (27,(55)(56)(57)(58)(59), with decreased expression of TNF receptor I (TNFRI), TNFRII, TRAILR-1, CD30 ligand, and Fas ( Figure 3C). In contrast, expression of the gene for IL-15R␣ chain was increased, whereas the gene for IL-2R␥ was decreased ( Figure 3C).…”
Section: Cd8ϩ T Cells In Scleroderma Lung Disease 2267mentioning
confidence: 99%
“…The other important proteins involved in this process include Fas, described also as TNF receptorsuperfamily member 6. Binding of ligand to Fas receptor between Band T cells may negatively modulate activation and proliferation of B cells, leading to induction of B cell apoptosis (12)(13). Furthermore, other molecules like interleukins (including in this study IL-l 0) belong to the family of proteins which are the main modulators of immune response and inflammatory reactions against foreign antigens (14)(15)(16).…”
mentioning
confidence: 99%